Basics of power system dynamics and stability - Renner, Herwig; Aristidou, Petros; Zhang, Ziqian (My University, 2024)
To operate an electricity grid in a stable manner, the same physical principles must be considered for interconnected and islanded operations. This chapter contains a brief overview of some of the basic concepts in power system dynamics and stability with a special focus on islanded grids. In the first section, general information about dynamics in power systems, including the main characteristics of devices concerning system dynamics, is given. In the following section, the formal definition of power system stability is presented, and the various types of power system stability are classified. Concerning the original classification, the new stability class converter-driven stability is introduced to cover the effects of the increasing penetration of fast-acting, converter-interfaced generation (CIG). In the following sub-sections, the different categories of system stability are presented. The dynamic behaviour of the power system is directly influenced by inertia and system strength. The level of inertia influences the frequency gradient (rate of change of frequency = RoCoF) and transient frequency values during a system incident. The impact of reduced system inertia on system operation is discussed in the following section. This decreased overall system inertia is caused by a shift of generation from classical synchronous generation to power electronic-based non-synchronous generation. Islanded systems usually have significantly reduced inertia. System strength is related to the inverse of the grid impedance. In classical power systems, dominated by synchronous machines, system strength corresponds to short-circuit capacity. In power systems with a high share of converter-based generation, short-circuit capacity as a measure of grid impedance during normal operation (close to nominal voltage) is different to short-circuit capacity during a fault. It strongly depends on control algorithms and the current limitation of connected inverters. Islanded systems usually have a significantly reduced system strength and inertia.
Intended and Unintended Islanding of Distribution Grids, Chapter 2
Keywords: power system dynamics; power system stability